Development of cementless mortar produced from calcined kaolin clay and granite dust powder with chemical activator - Al-Salman, Harith; Al-Rubaye, Muna M.; Owaid, Haider M. (Edelweiss Applied Science and Technology, 2025)
Geopolymers have garnered worldwide interest as an alternative binder to ordinary Portland cement (OPC) due to their environmental benefits, improved durability, and acceptable mechanical properties. Large amounts of aluminosilicate waste materials, often discarded and causing pollution, are generated globally. This study aims to develop a cementless binder (CLB) as a 100% OPC replacement by using pozzolanic and waste materials—calcined kaolin clay (CKC) and granite dust powder (GDP)—activated chemically with sodium hydroxide (NaOH). Six mortar mixes were prepared with CKC partially replaced by GDP at 0, 5, 10, 15, and 20% by weight. The mixtures were evaluated for various properties, including consistency, setting time, workability, bulk density, compressive strength, and flexural strength. Results showed increased consistency but decreased setting time and flow compared to conventional mortar. Setting time increased with higher GDP replacement. All alkali-activated CKC+GDP mixes demonstrated improved workability. The mixture containing 10% GDP exhibited the highest compressive strength (42.7 MPa) and flexural strength (6.69 MPa) after 28 days of air curing at 80°C, outperforming the control mixture. The findings suggest that the CLB developed with CKC and GDP activated chemically is a promising sustainable alternative to cement, especially for structures where early high strength is not critical. This approach can reduce cement demand, lower CO2 emissions, and mitigate environmental pollution by utilizing waste materials.